Popular description of the Diorama, the detail and principles of its arrangements and construction, and an examination of its pictures - Daguerre, Louis Jacques Mandé, 1787-1851 (Victorian popular culture. Moving pictures, optical entertainments and the advent of cinema., 2012)
Describes Daguerre's London Diorama in Regent's Park, and one of the exhibits, View of Brest Harbour.